2019
DOI: 10.1016/j.gexplo.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of nickel isotopes at the biogeochemical interface between ultramafic soils and Ni accumulator species

Abstract: Ultramafic derived soils are characterized by low nutrient soils, a low Ca:Mg ratio, and high metal contents such as Ni, Co and Cr. The vegetation growing on these soils is highly adapted and includes both Ni hyperaccumulator and accumulator species. Today, approximately 530 Ni hyperaccumulator species are listed worldwide and the Ni concentration can be extremely high, e.g. up to 25% in latex from Pycnandra acuminata (Sapotaceae), a tree found in New Caledonia. The aim of this study is to identify the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…• the presence of certain "hyperaccumulators" of metals (Ni) ( Jaffré et al 1976, Proctor and Nagy 1992, Reeves et al 2007, Kazakou et al 2008, Anacker 2014, Bini et al 2017, Kanellopoulos et al 2015, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…• the presence of certain "hyperaccumulators" of metals (Ni) ( Jaffré et al 1976, Proctor and Nagy 1992, Reeves et al 2007, Kazakou et al 2008, Anacker 2014, Bini et al 2017, Kanellopoulos et al 2015, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…, 2015; Ratié et al. , 2019). It has been suggested that plant isotopic composition is mainly controlled by the root uptake process (Estrade et al.…”
Section: Discussionmentioning
confidence: 99%
“…The use of multi‐collector inductively coupled plasma mass spectrometry (MC‐ICP‐MS) is increasingly used to investigate the fate and pathways of non‐traditional metals such as Ni in soil–plant systems through isotopic fractionation (Ratié et al. , 2019; Zelano et al. , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the above-mentioned Ni resource in soils per hectare would be completely depleted in 3 years of culture considering an annual yield of 142 kg Ni yr -1 after which the site will be suitable for other types of cropping. Research is currently underway to better understand the role of Ni hyperaccumulators in the geochemical cycle of Ni and the replenishment of Ni labile pools in soils over time Ratié et al, 2019). Intensive geochemical investigations are needed to determine the total extent of Ni-enriched substrates and to select the most suitable sites for Ni agromining in southeastern Mexico.…”
Section: Potential Sites For Agrominingmentioning
confidence: 99%